A method for preparing a thermal shock resistant polyimide aerogel insulation material
By introducing Kevlar nanofibers into polyimide aerogel and optimizing the preparation process, a nanoporous network structure is formed, which solves the problem of insufficient thermal shock resistance of polyimide aerogel in extreme environments and achieves high-efficiency thermal insulation performance and structural stability over a wide temperature range.
Patent Information
- Application Number
- CN202510946941.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2045-07-10
AI Technical Summary
Existing polyimide aerogel insulation materials have insufficient resistance to thermal shock in extreme environments, and their stability and structural integrity, especially in high and low temperature ranges, need to be improved.
Kevlar nanofibers were added during the preparation of polyimide aerogel, and by controlling the type and amount of dianhydride, diamine, and catalyst, combined with supercritical drying technology, a nanoporous network structure was formed to enhance its resistance to thermal shock.
The prepared thermal shock resistant polyimide aerogel insulation material exhibits low density, low thermal conductivity, and excellent thermal shock resistance in a temperature range of -196℃ to 400℃. The density is 0.103~0.286 g/cm3, the thermal conductivity is 0.0221~0.0324 W/(m·K), the cycle shrinkage rate is low, and the mass residue rate is high, meeting the extreme environmental requirements of the aerospace field.
Smart Images

Figure CN120424406B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of high-performance thermal insulation materials in the aerospace industry, specifically relating to a method for preparing a thermal shock resistant polyimide aerogel thermal insulation material. Background Technology
[0002] Aerogel materials, due to their high porosity, low density, and excellent thermal insulation properties, have been widely used in the aerospace thermal protection field. However, with the increasing diversification and complexity of application scenarios, more stringent requirements are being placed on high-performance aerogel materials. They must not only maintain stability in extreme environments such as high temperature, low temperature, and high radiation, but also possess excellent resistance to thermal shock, maintaining structural integrity and functional reliability during rapid temperature changes to ensure the safety and stability of advanced aircraft equipment throughout its entire life cycle.
[0003] Polyimide aerogel, as a high-performance polymer aerogel with great development potential, has emerged in the field of materials science due to its unique performance advantages. Polyimide itself possesses excellent thermal stability and mechanical properties, while also exhibiting the lightweight and low thermal conductivity characteristics of aerogel materials. It has gained widespread attention in the field of aerospace thermal protection. Chinese invention patent application (CN118909301A, publication date: 2024-11-08) reports a polyimide aerogel material that can be used at temperatures up to 420℃, with a thermal decomposition temperature reaching 700℃. It exhibits excellent high-temperature resistance, strong thermal stability (thermal conductivity at room temperature and pressure is 0.020~0.032W / (m·K)), and low density (0.09~0.20 g / cm³). 3 The material exhibits high strength (with a stress of 0.3–0.8 MPa under 3% compressive stress), but this invention does not mention its low-temperature resistance. Chinese invention patent (ZL 201910963604.9) reports a high- and low-temperature piezoresistive sensing polyimide composite aerogel with excellent resilience (after 100 cycles at -15°C with 50% compressive strain, the composite aerogel recovers 99% of its original height). Furthermore, its density is as low as 0.0175 g / cm³. 3 However, the patent does not cover research on the thermal shock resistance of polyimide aerogel.
[0004] Recently, Chun Liu et al. (Chun Liu, Mingkang Wang, Xin Zhao, et al. High-Temperature Resistant Polyimide AerogelsWithExtreme Condition Tolerance Constructed by In Situ Skeleton Encapsulation Growth. Advanced Functional Materials, (2025) Volume 25, Article 2500881) reported a polyimide aerogel with thermal shock resistance. The raw materials were ODA, 6FDA, and NMP solvents, which were mixed and stirred at room temperature until completely dissolved. A crosslinking agent was then added, and the final gel was obtained through sol-gel conversion and solution displacement, respectively. Finally, a polyimide aerogel with thermal shock resistance was obtained by supercritical CO2 drying. This product exhibits excellent thermal shock resistance (a cyclic shrinkage rate of only 1.09% and a mass residue rate of 95.46% within a temperature range of -196°C to 300°C) and a density as low as 0.11 g / cm³. 3 Its thermal conductivity is 0.0225 W / (m·K) to 0.0351 W / (m·K); however, its thermal insulation performance needs to be further improved, and its temperature range for resisting thermal shock is relatively narrow.
[0005] Therefore, how to further improve the thermal shock resistance of polyimide aerogel in extreme environments while ensuring that it has excellent properties such as low thermal conductivity and low density, and obtain a thermal shock resistant polyimide aerogel insulation material, is a key technical challenge that is of great concern to those skilled in the art. Summary of the Invention
[0006] To address the issues of narrow high-temperature range and insufficient thermal shock resistance in existing polyimide aerogel insulation materials, this invention provides a method for preparing a thermal shock resistant polyimide aerogel insulation material. By incorporating Kevlar nanofibers into the traditional polyimide aerogel preparation process and controlling the type and amount of dianhydride, diamine, catalyst, and Kevlar nanofibers, the mechanical properties are further improved, enhancing its thermal shock resistance and cyclic shrinkage characteristics, thus obtaining a thermal shock resistant polyimide aerogel insulation material.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A method for preparing a thermal shock resistant polyimide aerogel insulation material comprises the following steps:
[0009] S1. Under water bath stirring conditions, diamine and dianhydride are added to an organic solvent in a molar ratio of 1:0.8 to 1:2, and stirred for 20 to 50 minutes to obtain a polyamic acid solution.
[0010] S2. Add Kevlar nanofibers to the polyamic acid solution obtained in S1 and disperse them by ultrasonication to obtain a polyamic acid solution containing Kevlar nanofibers.
[0011] S3. Add a catalyst and a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in S2 to obtain a polyimide sol containing Kevlar nanofibers.
[0012] S4. After sealing the polyimide sol containing Kevlar nanofibers in S3, place it in a water bath at a temperature of 45℃-55℃ to gel the polyimide sol containing Kevlar nanofibers. The gelation time is 20-100 h to obtain the initial state gel of polyimide resistant to thermal shock.
[0013] S5. Place the thermal shock resistant polyimide pristine gel obtained in S4 in a high temperature environment of 50℃~80℃ and age it for 18~72h to obtain thermal shock resistant polyimide aged gel.
[0014] S6. The aged gel containing thermal shock resistant polyimide obtained in S5 is subjected to solvent replacement 2 to 5 times at room temperature (usually 25°C), each time for 2 to 12 hours, to obtain the final state gel of thermal shock resistant polyimide.
[0015] S7. The thermal shock resistant polyimide final state gel obtained in S6 is dried with supercritical CO2 fluid to obtain thermal shock resistant polyimide aerogel insulation material.
[0016] Preferably, the diamine in S1 is one or a mixture of several of p-phenylenediamine, 4,4'-diaminodiphenyl ether, and 4,4'-diamino-2,2'-dimethylbiphenyl; the dianhydride is one or a mixture of several of pyromellitic dianhydride, 4,4'-oxobisphthalic anhydride, and 3,3',4,4'-biphenyltetracarboxylic dianhydride; and the organic solvent is one or a mixture of several of dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0017] Preferably, the ultrasonic dispersion in step S2 has a power of 100~500W, a frequency of 20~80kHz, a temperature of 20~50℃, and a time of 10~60min.
[0018] Preferably, the Kevlar nanofibers in S3 have a diameter of 15-30 nm and a length of 1.5-3.5 μm; the catalyst is one of methylpyridine, triethylamine, or pyridine; and the crosslinking agent is one of 1,3,5-tris(4-aminophenyl)benzene, triphenylmethane triisocyanate, 1,3,5-benzenetricarboxyl chloride, or 1,3,5-tris(4-aminophenoxy)benzene.
[0019] More preferably, the molar ratio of the Kevlar nanofibers, catalyst, crosslinking agent, and diamine is (0.10~0.20):(0.01~0.015):(0.01~0.015):1;
[0020] Preferably, the temperature in the water bath during step S4 is 50°C.
[0021] Preferably, the organic solvent in S6 is one or a mixture of methanol, ethanol or isopropanol; the number of solvent replacements is preferably 3, and the replacement time for each replacement is preferably 10 hours.
[0022] Preferably, the pressure of CO2 supercritical fluid drying in S7 is 12~25 MPa, the temperature is 50~70℃, the drying time is 8~20 h, and the pressure is released at a rate of 90~140 kPa / min after drying is completed.
[0023] The beneficial effects of this invention are:
[0024] 1. In the second step (S2) of the preparation method of the thermal shock resistant polyimide aerogel insulation material of this invention, Kevlar nanofibers are innovatively added. Kevlar fibers themselves have excellent high and low temperature resistance (-196℃-400℃) and excellent mechanical properties. After being combined with polyimide aerogel, they can effectively improve the material's thermal shock resistance. Furthermore, a crosslinking agent is added to introduce a crosslinking structure to reinforce and modify the polyimide aerogel (S3), further improving the skeletal strength and flexibility of the polyimide aerogel. At the same time, a supercritical drying method is used (S7) to give the material a nanoporous network structure, thereby endowing the thermal shock resistant polyimide aerogel insulation material with lightweight and high-efficiency thermal insulation properties.
[0025] 2. The thermal shock resistant polyimide aerogel insulation material prepared by the method of this invention exhibits low density, low thermal conductivity, and excellent thermal shock resistance. Its density ranges from 0.103 to 0.286 g / cm³. 3With a thermal conductivity of 0.0221~0.0324 W / (m·K), it can withstand ambient temperatures ranging from -196℃ to 400℃. Under both low and high temperature conditions, its dimensional and thickness cyclic shrinkage is as low as 0.15%~0.56%, and its mass residue is 91.2%~93.5%. Its excellent overall performance effectively meets the current aerospace industry's demand for high-performance organic thermal protection materials resistant to thermal shock in extreme environments. Attached Figure Description
[0026] Figure 1 This is a flowchart illustrating the preparation method of the thermal shock resistant polyimide aerogel high thermal insulation material of the present invention.
[0027] Figure 2 The macroscopic morphology of the thermal shock resistant polyimide aerogel high thermal insulation material of the present invention is shown.
[0028] Figure 3 This is the microstructure of the thermal shock resistant polyimide aerogel high thermal insulation material of the present invention;
[0029] Figure 4 The microstructure of polyimide aerogel insulation material without Kevlar fiber is shown. Detailed Implementation
[0030] Example 1:
[0031] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:0.8 under water bath stirring conditions, and stir for 20 minutes to obtain a polyamic acid solution.
[0032] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, and then subjecting it to ultrasonic dispersion at a power of 100 W, a frequency of 20 kHz, a temperature of 20 °C, and a time of 20 min. This yields a polyamic acid solution containing Kevlar nanofibers.
[0033] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0034] In the fourth step, the polyamic acid sol containing Kevlar nanofibers prepared in the third step was sealed and placed in a water bath at a gelation temperature of 45°C to gel the polyamic acid sol containing Kevlar nanofibers for 20 hours. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.01:0.01:0.01:1 to obtain the initial state gel of thermal shock resistant polyimide.
[0035] Fifth step: Place the thermal shock resistant polyimide pristine gel obtained in the fourth step in a high temperature environment of 50°C and age it for 18 hours to obtain thermal shock resistant polyimide aged gel.
[0036] Step 6: The polyamic acid aged gel containing Kevlar nanofibers obtained in step 5 is subjected to solvent replacement twice at room temperature for 12 hours each time to obtain the thermal shock resistant polyimide final state gel.
[0037] Step 7: The thermal shock resistant polyimide final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 12 MPa, the temperature is 50℃, and the drying time is 8h. After drying, the pressure is released at a rate of 90 kPa / min to obtain thermal shock resistant polyimide aerogel insulation material.
[0038] The macroscopic morphology of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is as follows: Figure 2 As shown, it has the characteristics of being lightweight and high-strength, and its microstructure is as follows. Figure 3 As shown, the polyimide aerogel has a relatively large particle size and is tightly bonded to Kevlar fibers, giving it resistance to thermal shock. Its density is 0.103 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0221 W / (m·K). When the temperature range is -100~400℃, after thermal shock testing, the cyclic shrinkage rate of size and thickness is 0.56%, and the mass residue rate is 91.5%.
[0039] Example 2:
[0040] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:0.9 under water bath stirring conditions, and stir for 24 minutes to obtain a polyamic acid solution.
[0041] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, and then subjecting it to ultrasonic dispersion at a power of 150 W, a frequency of 25 kHz, a temperature of 24 °C, and a time of 30 min. This yields a polyamic acid solution containing Kevlar nanofibers.
[0042] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0043] In the fourth step, the polyamic acid sol containing Kevlar nanofibers prepared in the third step was sealed and placed in a water bath at a gelation temperature of 46°C to gel the polyamic acid sol containing Kevlar nanofibers for 25 hours. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.11:0.0105:0.011:1 to obtain a resistant thermal shock initial state gel.
[0044] Fifth step: Place the thermal shock resistant polyimide pristine gel obtained in the fourth step in a high temperature environment of 55°C for 36 hours to obtain thermal shock resistant polyimide aged gel.
[0045] Step 6: The thermal shock resistant polyimide aged gel obtained in step 5 is subjected to solvent replacement 4 times at room temperature, each time for 11 hours, to obtain the thermal shock resistant polyimide final gel.
[0046] Step 7: The thermal shock resistant polyimide final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 13 MPa, the temperature is 55℃, and the drying time is 9 hours. After drying, the pressure is released at a rate of 95 kPa / min to obtain thermal shock resistant polyimide aerogel insulation material.
[0047] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.123 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0238 W / (m·K). The cyclic shrinkage rate of size and thickness is 0.49% when the temperature range is -100~400℃, and the mass residue rate is 91.7%.
[0048] Example 3:
[0049] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:1 under water bath stirring conditions, and stir for 26 minutes to obtain a polyamic acid solution.
[0050] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, followed by ultrasonic dispersion at a power of 200 W, a frequency of 35 kHz, a temperature of 28 °C, and a time of 40 min. This yields a polyamic acid sol containing Kevlar nanofibers.
[0051] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0052] In the fourth step, the polyamic acid sol containing Kevlar nanofibers obtained in the third step was sealed and placed in a water bath at a gelation temperature of 47°C to gel the polyamic acid sol containing Kevlar nanofibers for 35 hours. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.12:0.011:0.0115:1 to obtain a thermal shock resistant polyamic acid sol in its initial state.
[0053] Fifth step: Place the thermal shock resistant polyimide pristine gel obtained in the fourth step in a high temperature environment of 60°C for 45 hours to obtain thermal shock resistant polyamic acid aged gel.
[0054] Step 6: The thermal shock resistant polyimide aged gel obtained in step 5 is subjected to solvent replacement 6 times at room temperature for 10 hours each time to obtain the thermal shock resistant polyamic acid final gel.
[0055] Step 7: The thermal shock resistant polyimide final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 14 MPa, the temperature is 57℃, and the drying time is 10h. After drying, the pressure is released at a rate of 100kPa / min to obtain thermal shock resistant polyimide aerogel insulation material.
[0056] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.154 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0249 W / (m·K). The cyclic shrinkage rate of size and thickness is 0.43% when the temperature range is -100~400℃, and the mass residue rate is 91.9%.
[0057] Example 4:
[0058] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:1.2 under water bath stirring conditions, and stir for 30 minutes to obtain a polyamic acid solution.
[0059] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, followed by ultrasonic dispersion at a power of 250 W, a frequency of 45 kHz, a temperature of 32 °C, and a time of 50 min. This yields a polyamic acid sol containing Kevlar nanofibers.
[0060] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0061] In the fourth step, the polyimide sol containing Kevlar nanofibers obtained in the third step was sealed and placed in a water bath at a gelation temperature of 48°C to gel the polyamic acid sol containing Kevlar nanofibers for 40 hours. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.13:0.0115:0.012:1 to obtain a preliminary gel containing polyamic acid resistant to thermal shock.
[0062] Fifth step: Place the thermal shock resistant polyamic acid pristine gel obtained in the fourth step in a high temperature environment of 65°C for 50 hours to obtain thermal shock resistant polyamic acid aged gel.
[0063] Step 6: The thermal shock resistant polyamic acid aged gel obtained in step 5 is subjected to solvent replacement 8 times at room temperature, each time for 9 hours, to obtain the thermal shock resistant polyamic acid final gel.
[0064] Step 7: The thermal shock resistant polyamic acid final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 15 MPa, the temperature is 60℃, and the drying time is 12h. After drying, the pressure is released at a rate of 110kPa / min to obtain thermal shock resistant polyamic acid aerogel insulation material.
[0065] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.176 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0265 W / (m·K). The cyclic shrinkage rate of size and thickness is 0.32% when the temperature range is -100~400℃, and the mass residue rate is 92.1%.
[0066] Example 5:
[0067] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:1.4 under water bath stirring conditions, and stir for 32 minutes to obtain a polyamic acid solution.
[0068] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, followed by ultrasonic dispersion at a power of 300 W, a frequency of 50 kHz, a temperature of 40 °C, and a time of 60 min. This yields a polyamic acid sol containing Kevlar nanofibers.
[0069] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0070] In the fourth step, the polyimide sol containing Kevlar nanofibers obtained in the third step was sealed and placed in a water bath at a gelation temperature of 49°C to gel the polyamic acid sol containing Kevlar nanofibers for 50 hours. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate, and diamine was 0.14:0.012:0.0125:1.
[0071] A resistant polyamic acid gel in its initial state was obtained;
[0072] Fifth step: Place the thermal shock resistant polyamic acid pristine gel obtained in the fourth step in a high temperature environment of 70°C for 55 hours to obtain thermal shock resistant polyamic acid aged gel.
[0073] Step 6: The thermal shock resistant polyamic acid aged gel obtained in step 5 is subjected to solvent replacement 10 times at room temperature for 8 hours each time to obtain the thermal shock resistant polyamic acid final gel.
[0074] Step 7: The final state gel of the thermal shock resistant polyamic acid from step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 16 MPa, the temperature is 62℃, and the drying time is 14h. After drying, the pressure is released at a rate of 115kPa / min to obtain the thermal shock resistant polyamic acid aerogel insulation material.
[0075] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.188 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0271 W / (m·K). The cyclic shrinkage rate of size and thickness is 0.28% when the temperature range is -100~400℃, and the mass residue rate is 92.4%.
[0076] Example 6:
[0077] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:1.6 under water bath stirring conditions, and stir for 36 minutes to obtain a polyamic acid solution.
[0078] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, followed by ultrasonic dispersion at a power of 350 W, a frequency of 65 kHz, a temperature of 42 °C, and a time of 70 min. This yields a polyamic acid sol containing Kevlar nanofibers.
[0079] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0080] In the fourth step, the polyimide sol containing Kevlar nanofibers obtained in the third step was sealed and placed in a water bath at a gelation temperature of 50°C to gel the polyamic acid sol containing Kevlar nanofibers for 60 hours. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.15:0.0125:0.0130:1 to obtain a thermal shock resistant polyamic acid sol in its initial state.
[0081] The fifth step is to place the thermal shock resistant polyamic acid pristine gel obtained in the fourth step in a high temperature environment of 72°C for 60 hours to obtain thermal shock resistant polyamic acid aged gel.
[0082] Step 6: The thermal shock resistant polyamic acid aged gel obtained in step 5 is subjected to solvent replacement 12 times at room temperature, each time for 6 hours, to obtain the thermal shock resistant polyamic acid final gel.
[0083] Step 7: The thermal shock resistant polyamic acid final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 18 MPa, the temperature is 64℃, and the drying time is 15h. After drying, the pressure is released at a rate of 120kPa / min to obtain thermal shock resistant polyamic acid aerogel insulation material.
[0084] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.226 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0290 W / (m·K). The cyclic shrinkage rate of size and thickness is 0.24% when the temperature range is -100~400℃, and the mass residue rate is 92.6%.
[0085] Example 7:
[0086] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:1.8 under water bath stirring conditions, and stir for 40 minutes to obtain a polyamic acid solution.
[0087] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, followed by ultrasonic dispersion at a power of 400 W, a frequency of 70 kHz, a temperature of 46 °C, and a time of 80 min. This yields a polyamic acid sol containing Kevlar nanofibers.
[0088] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0089] In the fourth step, the polyimide sol containing Kevlar nanofibers obtained in the third step was sealed and placed in a water bath at a gelation temperature of 51°C to gel the polyamic acid sol containing Kevlar nanofibers for 70 hours. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.16:0.013:0.0135:1 to obtain a thermal shock resistant polyamic acid sol in its initial state.
[0090] Fifth step: Place the thermal shock resistant polyamic acid pristine gel obtained in the fourth step in a high temperature environment of 75°C for 64 hours to obtain thermal shock resistant polyamic acid aged gel.
[0091] Step 6: The thermal shock resistant polyamic acid aged gel obtained in step 5 is subjected to solvent replacement 13 times at room temperature for 15 hours each time to obtain the thermal shock resistant polyamic acid final gel.
[0092] Step 7: The thermal shock resistant polyamic acid final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 20 MPa, the temperature is 66℃, and the drying time is 16 h. After drying, the pressure is released at a rate of 125 kPa / min to obtain thermal shock resistant polyamic acid aerogel insulation material.
[0093] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.245 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0308 W / (m·K), the cyclic shrinkage rate of size and thickness is 0.21%, and the mass residue rate is 92.9%.
[0094] Example 8:
[0095] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:1.9 under water bath stirring conditions, and stir for 45 minutes to obtain a polyamic acid solution.
[0096] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, followed by ultrasonic dispersion at a power of 450 W, a frequency of 75 kHz, a temperature of 48 °C, and a time of 90 min. This yields a polyamic acid sol containing Kevlar nanofibers.
[0097] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0098] In the fourth step, the polyimide sol containing Kevlar nanofibers obtained in the third step was sealed and placed in a water bath at a gelation temperature of 54°C to gel the polyamic acid sol containing Kevlar nanofibers for 80 h. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.18:0.014:0.014:1 to obtain a thermal shock resistant polyamic acid sol in its initial state.
[0099] Fifth step: Place the thermal shock resistant polyamic acid pristine gel obtained in the fourth step in a high temperature environment of 78°C and age it for 70 hours to obtain thermal shock resistant polyamic acid aged gel.
[0100] Step 6: The thermal shock resistant polyamic acid aged gel obtained in step 5 is subjected to solvent replacement 14 times at room temperature for 3 hours each time to obtain the thermal shock resistant polyamic acid final gel.
[0101] Step 7: The thermal shock resistant polyamic acid final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 24 MPa, the temperature is 68℃, and the drying time is 18h. After drying, the pressure is released at a rate of 130kPa / min to obtain thermal shock resistant polyamic acid aerogel insulation material.
[0102] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.266 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0311 W / (m·K), and the cyclic shrinkage rate of size and thickness is 0.19% when the temperature range is -100~400℃, with a mass residue rate of 93.1%.
[0103] Example 9:
[0104] The first step is to add p-phenylenediamine and pyromellitic dianhydride to a dimethylacetamide solution in a molar ratio of 1:2 under water bath stirring conditions, and stir for 50 minutes to obtain a polyamic acid solution.
[0105] The second step involves adding Kevlar nanofibers to the polyamic acid solution obtained in the first step to obtain a polyamic acid solution containing Kevlar, followed by ultrasonic dispersion at a power of 500 W, a frequency of 80 kHz, a temperature of 50 °C, and a time of 100 min. This yields a polyamic acid sol containing Kevlar nanofibers.
[0106] The third step involves adding methylpyridine as a catalyst and triphenylmethane triisocyanate as a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in the second step to obtain a polyimide sol containing Kevlar nanofibers.
[0107] In the fourth step, the polyimide sol containing Kevlar nanofibers obtained in the third step was sealed and placed in a water bath at a gelation temperature of 55°C to gel the polyamic acid sol containing Kevlar nanofibers for 100 h. The molar ratio of Kevlar nanofibers, methylpyridine, triphenylmethane triisocyanate and diamine was 0.2:0.015:0.015:1 to obtain the initial state gel of polyamic acid resistant to thermal shock.
[0108] Fifth step: Place the thermal shock resistant polyamic acid pristine gel obtained in the fourth step in a high temperature environment of 80°C for 72 hours to obtain thermal shock resistant polyamic acid aged gel.
[0109] Step 6: The thermal shock resistant polyamic acid aged gel obtained in step 5 is subjected to solvent replacement 15 times at room temperature for 2 hours each time to obtain the thermal shock resistant polyamic acid final gel.
[0110] Step 7: The thermal shock resistant polyamic acid final state gel obtained in step 6 is subjected to supercritical CO2 drying. The pressure of supercritical CO2 drying is 25 MPa, the temperature is 70℃, and the drying time is 20h. After drying, the pressure is released at a rate of 140kPa / min to obtain thermal shock resistant polyamic acid aerogel insulation material.
[0111] The density of the thermal shock resistant polyimide aerogel insulation material prepared in this embodiment is 0.286 g / cm³. 3 The thermal conductivity at room temperature and pressure is 0.0324 W / (m·K). The cyclic shrinkage rate of size and thickness is 0.15 when the temperature range is -100~400℃, and the mass residue rate is 93.5%.
[0112] In this invention, as long as the gelation temperature, aging time, solvent type, number of replacements, and replacement time are within the specified ranges, the effects of these factors on the density, thermal conductivity, compressive strength, and thermal shock resistance of the thermal shock resistant polyimide aerogel can be largely ignored. The density, thermal conductivity, and mechanical strength of the thermal shock resistant polyimide aerogel are mainly affected by the molar ratio of diamine to dianhydride and the amount of Kevlar fiber added. Specifically, a higher molar ratio of diamine to dianhydride results in a higher density, higher thermal conductivity, and stronger mechanical strength of the polyimide aerogel; a higher amount of Kevlar fiber also results in a higher density, higher thermal conductivity, stronger mechanical strength, and better thermal shock resistance; and a greater amount of Kevlar nanofibers results in a higher density, higher thermal conductivity, stronger mechanical strength, and better thermal shock resistance.
[0113] Comparative Example 1
[0114] The difference between Comparative Example 1 and Example 1 is that the addition of Kevlar nanofibers in the second step is absent; otherwise, they are the same as in Example 1.
[0115] The density of the obtained polyimide aerogel containing Kevlar nanofibers was 0.09 g / cm³. -3 The thermal conductivity is 0.020 W / m. -1 K -1 However, under extreme conditions, the internal structure of polyimide aerogel collapses.
[0116] The results show that the introduction of Kevlar nanofibers can improve the thermal shock resistance of polyimide aerogel insulation materials. Figure 4 The microstructure of polyimide aerogel without Kevlar fibers is characterized by a fine network structure, resulting in relatively low density and thermal conductivity, but also poor resistance to thermal shock.
[0117] Comparative Example 2:
[0118] The difference between Comparative Example 2 and Example 2 is that the mass ratio of Kevlar nanofibers to polyimide fibers added in the second step is 0.05:1, otherwise it is the same as Example 2; the density of the resulting polyimide aerogel containing Kevlar nanofibers is 0.232 g / cm³. -3 The thermal conductivity is 0.0444 W / m. -1 K -1 The cyclic shrinkage rate of size and thickness under extreme environments is 0.7%;
[0119] The results show that a high mass ratio of Kev nanofibers to polyimide nanofibers (above 0.2:1) leads to a decrease in the cyclic shrinkage rate of size and thickness under extreme environments. While polyimide aerogel insulation materials can achieve higher mechanical strength, their density and thermal conductivity increase, making them unsuitable for high-efficiency insulation applications.
[0120] Comparative Example 3
[0121] The difference between Comparative Example 3 and Example 3 is that the molar ratio of p-phenylenediamine and pyromellitic dianhydride is 1:3 (greater than 1:2), while the rest is the same as in Example 1. However, it is difficult to obtain a stable thermal shock resistant polyimide aerogel.
[0122] The results showed that polyimide nanofiber aerogels could not be obtained when the mass ratio of dianhydride to diamine exceeded the range of 1:0.8 to 1:2.
[0123] The above are merely preferred embodiments of the present invention. The scope of protection of the present invention is not limited to the above embodiments. Various process solutions that are not substantially different from the concept of the present invention are all within the scope of protection of the present invention.
Claims
1. An application of a polyimide aerogel in improving the thermal shock resistance of materials, characterized in that, The preparation method of the polyimide aerogel includes the following steps: S1. Under water bath stirring conditions, diamine and dianhydride are added to an organic solvent in a molar ratio of 1:0.8 to 1:2, and stirred for 20 to 50 minutes to obtain a polyamic acid solution. S2. Add Kevlar nanofibers to the polyamic acid solution obtained in S1 and disperse them by ultrasonication to obtain a polyamic acid solution containing Kevlar nanofibers. S3. Add a catalyst and a crosslinking agent to the polyamic acid solution containing Kevlar nanofibers obtained in S2 to obtain a polyimide sol containing Kevlar nanofibers. S4. After sealing the polyimide sol containing Kevlar nanofibers in S3, place it in a water bath at a temperature of 45℃-55℃ to gel the polyimide sol containing Kevlar nanofibers. The gelation time is 20-100 h to obtain the initial state gel of polyimide resistant to thermal shock. S5. Place the thermal shock resistant polyimide pristine gel obtained in S4 in a high temperature environment of 50℃~80℃ and age it for 18~72h to obtain thermal shock resistant polyimide aged gel. S6. The thermal shock resistant polyimide aged gel obtained in S5 is subjected to solvent replacement 2 to 5 times at room temperature, each time for 2 to 12 hours, to obtain the thermal shock resistant polyimide final gel. S7. The thermal shock resistant polyimide final state gel obtained in S6 is dried with supercritical CO2 fluid to obtain thermal shock resistant polyimide aerogel insulation material.
2. The application of the polyimide aerogel according to claim 1 in improving the thermal shock resistance of materials, characterized in that: The diamine mentioned in S1 is one or a mixture of several of p-phenylenediamine, 4,4'-diaminodiphenyl ether, and 4,4'-diamino-2,2'-dimethylbiphenyl; the dianhydride is one or a mixture of several of pyromellitic dianhydride, 4,4'-oxobisphthalic anhydride, and 3,3',4,4'-biphenyltetracarboxylic dianhydride; and the organic solvent is one or a mixture of several of dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
3. The application of the polyimide aerogel according to claim 1 in improving the thermal shock resistance of materials, characterized in that: The ultrasonic dispersion in S2 has a power of 100~500W, a frequency of 20~80kHz, a temperature of 20~50℃, and a time of 10~60min.
4. The application of the polyimide aerogel according to claim 1 in improving the thermal shock resistance of materials, characterized in that: The Kevlar nanofibers in S3 have a diameter of 15-30 nm and a length of 1.5-3.5 μm; the catalyst is one of methylpyridine, triethylamine, or pyridine; and the crosslinking agent is one of 1,3,5-tris(4-aminophenyl)benzene, triphenylmethane triisocyanate, 1,3,5-benzenetricarboxyl chloride, or 1,3,5-tris(4-aminophenoxy)benzene.
5. The application of the polyimide aerogel according to claim 4 in improving the thermal shock resistance of materials, characterized in that: The molar ratio of the Kevlar nanofibers, catalyst, crosslinking agent and diamine is (0.10~0.20):(0.01~0.015):(0.01~0.015):
1.
6. The application of the polyimide aerogel according to claim 1 in improving the thermal shock resistance of materials, characterized in that: The temperature in the water bath in S4 is 50°C.
7. The application of the polyimide aerogel according to claim 1 in improving the thermal shock resistance of materials, characterized in that: The organic solvent in S6 is one or a mixture of methanol, ethanol or isopropanol; the solvent is replaced three times, and each replacement takes 10 hours.
8. The application of the polyimide aerogel according to claim 1 in improving the thermal shock resistance of materials, characterized in that: The supercritical CO2 fluid drying process in S7 is carried out at a pressure of 12-25 MPa, a temperature of 50-70℃, and a drying time of 8-20 h. After drying, the pressure is released at a rate of 90-140 kPa / min.
Citation Information
Patent Citations
A high and low temperature piezoresistive sensing polyimide composite aerogel and its preparation method
CN110776741B
High-temperature-resistant polyimide aerogel composite material as well as preparation method and application thereof
CN118909301A
Preparation method of chopped fiber layered reinforced polyimide aerogel
CN113024883A
Organic polymer aerogels comprising microstructures
US20190390025A1